2010
DOI: 10.1111/j.1834-7819.2010.01259.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bleaching versus repolishing on colour and surface topography of stained resin composite

Abstract: Background: The aim of this study was to examine the effect of ozonated gel, carbamide peroxide bleaching agent and polishing paste on the colour and surface topography of stained resin composite. Methods: Ninety disc-shaped resin composite specimens were used in this study. They were randomly divided into three groups of 30 specimens each according to the immersion solutions used, i.e., tea, cola or artificial saliva. Each group was further subdivided into three equal subgroups (n = 10) according to the type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 26 publications
(32 reference statements)
1
30
0
2
Order By: Relevance
“…Currently, no single in vitro test can simultaneously simulate all of these parameters. [2][3][4][5][6][7] Recent investigations have shown that the initial bonding effectiveness of contemporary adhesives is quite favorable regardless of the approach used. However, in terms of long-term clinical service, the bonding effectiveness of tooth restoration interfacial joints is questionable.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, no single in vitro test can simultaneously simulate all of these parameters. [2][3][4][5][6][7] Recent investigations have shown that the initial bonding effectiveness of contemporary adhesives is quite favorable regardless of the approach used. However, in terms of long-term clinical service, the bonding effectiveness of tooth restoration interfacial joints is questionable.…”
Section: Introductionmentioning
confidence: 99%
“…Tea, coffee, and soft drinks are highly popular drinks in today's world, especially in industrialized countries. It has been demonstrated that surface discolorations in composite resins are related to hygiene and eating habits, as well as smoking status (12). Maintaining the esthetics of a restoration is therefore related to the patient's habits and lifestyle (1).…”
Section: Introductionmentioning
confidence: 99%
“…Roughness studies involving immersion in dental bleaching agents and soft drinks have been performed only on dental enamel, composite resin, acrylic resin and other materials for dental restorations . These studies observed the values of the roughness profile (Ra) and surface characterization (SEM and AFM), concluding that the dental bleaching agents and cola soft drinks induced variations in the surface roughness of the dental materials.…”
Section: Discussionmentioning
confidence: 99%